KEPEMIMPINAN PENGHULU PEREMPUAN DALAM PEMERINTAHAN KEPENGHULUAN BANGKO SEMPURNA KECAMATAN - Anshori, M. Wira; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This view of women has changed a lot due to the progress of time. One woman's success can be seen from the leadership of a woman. Women's achievements and success proves that women also have much in common with the man. Even may exceed the capabilities of man. The involvement of women in public office filling the post-reform experience significant development in Indonesia. Since Indonesia using the system of regional autonomy, many strategic positions, such as governors, regents, and the village chief held by women.In this study, the method used is qualitative approach. While the data analysis technique used is descriptive analysis of spoken words and observable behavior of the people studied. This research was conducted in Rokan Hilir in Riau Province. While the object of this study is Kepenghuluan Bangko Perfect, with a focus on women's leadership in governance prince kepenghuluan views of nature along with the factors that affect the success of women's leadership prince. The theory used is the theory put forward by Keith Davis.Based on the results of research conducted and followed by analyzing the data obtained through interviews, observation, and documentation. After doing some research, the authors conclude the first period had been made: Opening of roads and streets Kepenghuluan Paving, Electrical Entering the Village of provincial government programs, services to the community kepenghuluan Implementation, Development Bangko Perfect kepenghuluan office and village hall, Being a winner in the race's best village Rokan Hilir. In the second period has been made: Acquisition of land and make the rural market for the economy, society, Back insert Electric Village of Provincial Government Programs, Extract parts of Bangko kepenghuluan Perfect, Getting government assistance for the development of appropriate housing, street Semenisasi kepenghuluan. As well as factors that affect the success of the prince of female leadership: intelligence, maturity and flexibility of social relationships, self motivation and encouragement of achievement, attitudes human relations.Keywords: Leadership, Leadership Traits, prince of Women